Charitable Work of the Church in the Polish Lands in the XIX Century and its Impact on Education - Leszek Aftyka; Piotr Mazur (Vasyl Stefanyk Precarpathian National University, 2020)
The Catholic Church in the Polish lands in the XIX century has had numerous charity works. The charitable activities were seen as the task of God's commandment of love. The purpose of this activity was to support poor people in the form of satisfying basic material needs and achieving adequate personal development. The article discusses the most important forms of assistance provided by religious orders, as well as clerical and lay organizations. The author draws attention to the charity's impact on education and the formation of humanistic values in society. Many priests set up organisations that had such names as: "Star", "Aurora", "Fatherland", "Rock". Their main objective was to raise up education standards and stimulate patriotism and solidarity among young people. Therefore, cooperation between educational institutions, families, non-governmental organizations, volunteer movements, charitable foundations for the expansion of active charitable activities, and the creation of a humanistic society is required. Nowadays it is extremely important to revive philanthropy and altruism in every country. Currently, there are foundations, organizations aimed at carrying out charitable activities and attracting to the charity all who wish to serve the cause of raising Christian morality, culture, education, art, support of the poor. Thus, this is important to promote it in the educational field as well. After all, many young people are ready to help financially or spiritually those who need it; they seek to invest time, money and talent into a rapidly growing charity. Here we see an important role of the Catholic Church, which influences the development of the spirituality of the individual.